Squamous Cell Carcinoma of Renal Pelvis: Can Calculi Be Life Threatening? - Batra, Harsh; Ahluwalia, Charanjeet; Yadav, Amit; Dhawan, Indrani (Annals of Pathology and Laboratory Medicine, 2018)
Primary squamous cell carcinoma of renal pelvis is a rare neoplasm that is associated with infection and renal calculi. These tumors are highly aggressive and present at an advanced stage. We report a case of primary squamous cell carcinoma of renal pelvis in a 40-year old man, who presented with a left sided painful renal pelvic mass with a history of renal calculi 7 years ago. He was worked up with a CECT abdomen which showed a heterogeneously enhancing lesion and renal calculi in the left kidney. After radical nephrectomy, histopathological examination revealed squamous cell carcinoma of renal pelvis. SCC should be suspected in a patient with long history of renal calculus and associated mass in kidney.